Understanding customer expectations towards a hostel : case Ibedcity hostel - Ly, Cao (2023)
In recent years, travelling demand has bounced back stronger than ever, especially after many restrictions from COVID-19 time. Running parallel with benefiting from the rising needs, tourism entrepreneurs have to face many challenges regarding service quality management. Despite paying the same price, travellers tend to have different expectations and experiences for the received services. To shed more light on this matter, the thesis has been conducted. The primary goal of this thesis project is to further understand customer expectations towards one particular type of accommodation: a hostel. In addition, re-search on Rovaniemi destination as well as competitors were also studied to locate the company’s competitive edge. Based on the analysed data, the author suggested a development plan to support the business’s management process. The commissioner of the thesis is Ibecity Hostel, located in Rovaniemi, Finland. Service quality is always one of the top priorities since the company’s establishment. The mixed-method research was approached as the main methodology for this project. The data collection process starts with analyzing both quantitatively and qualitatively the guest reviews of Ibedcity Hostel on Booking.com. Furthermore, a semi-structured interview and participant observation were also conducted to gain more insights into the business operations. With the data acknowledged from this project, it supposedly brings good insights for Ibedcity Hostel to improve its service quality as well as enhance the company's competitiveness.